Engineered bone-targeting apoptotic vesicles as a minimally invasive nanotherapy for heterotopic ossification - Like Tang; Yuchen Wang; Shihua Mao; Zhou Yu; Yitong Chen; Xiaoqiao Xu; Wenjin Cai; Kaichen Lai; Guoli Yang; Tingben Huang (Journal of Nanobiotechnology)
Abstract Heterotopic Ossification (HO), refers to pathological extra skeletal bone formation, and there are currently no reliable methods except surgery to reverse these unexpected calcified tissues. Apoptotic vesicles (ApoEVs) are membrane-bound vesicles released by apoptotic cells, which are involved in metabolism regulation and intercellular communication. Due to its superior trauma-healing ability, the hard palate mucosa is expected to become an essential resource for tissue engineering. This work presents a minimally invasive nanotherapy based on an engineered apoEV. Briefly, apoEVs were extracted from hard palate mucosa and engineered with bone-targeting peptide SDSSD to treat HO. This engineered apoEV not only can achieve directed localization of heterotopic bones but also has the compelling dual function of promoting osteoclastic differentiation while inhibiting osteogenic differentiation. The underlying mechanism involves the activation of Hippo and Notch pathways, as well as the regulation of pyrimidine metabolism. We envision that this engineered apoEV may be a feasible and effective strategy for reversing HO. Graphical Abstract